PENERAPAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI SISWA KELAS VII5 SMP NEGERI 14 PEKANBARU TAHUN AJARAN 2012/2013 - Mariani Natalina; Nursal '; Srini ' (Program Studi Pendidikan Biologi, 2013)
This research is a classroom action research that aims to improve the biological activity and learning outcomes of students with learning model Cooperative Script implementation on SMP VII5 class Pekanbaru 14 Academic Year 2012/2013. The research was conducted in April-May 2013. The subjects were 14 grade students VII5 SMP Pekanbaru, amounting to 32 people (15 students and 17 female students). Parameters measured were student activity consisting of 6 indicators and student learning outcomes consisting of absorption, mastery learning of individual students as well as teachers' activities. The average activity of students in the first cycle is 78.75% (average) increase in cycle II with an average activity of students is 91.92% (excellent). Absorption of students in the first cycle is 77.56 (enough) increased to 82.75 (enough). Mastery learning students in the first cycle is 59.38% (completed) increased in the second cycle to 81.25% (complete). Teachers activities in the first cycle with the average of 94.4% (very good) increased in the second cycle is 95.8% (very good). From the research it can be concluded that the application of learning models Cooperative Script can increase the activity and student learning outcomes biology class Pekanbaru VII5 SMP 14 Academic Year 2012/2013.Keywords: Coopertaif Script, student activities, Biology Learning Outcom